New species of Bryconamericus Eigenmann (Characiformes: Characidae) from the rio Teles Pires, rio Tapajós basin, central Brazil - Dagosta, Fernando C. P.; Dagosta, P.; Netto-Ferreira, André L. (Zootaxa, 2015)
A new species of Bryconamericus is described from the rio Teles Pires, a tributary of the rio Tapajós. The new taxon can be distinguished from its congeners by having a short anal fin with 11–13 branched rays, two maxillary teeth, four outer premaxillary teeth, and 34–38 perforated lateral-line scales. Other diagnostic characters of the species are the absence of a caudal-peduncle spot and the presence of a pigmented vertical band at the caudal-fin rays base. The phylogenetic position of the new species is inferred based in two available phylogenetic hypotheses, and a discussion on its generic placement is provided.